The evolution mechanism of the cyber-physical cascading failure of power distribution system based on event-driven - HUANG Zhi; LIU Dong; CHEN Guanhong; WENG Jiaming; YIN Haoyang; WANG Zhen (电力工程技术, 2022)
With the rapid development of communication and control technology in power distribution system,it has gradually shown the typical characteristics of cyber-physical systems,which not only brings new opportunities for development,but also brings multiple types of risks in the information system to the power system. As a result,cyber-physical cascading failures in the power system have occurred frequently,leading to serious accidents. Therefore,analyzing and studying the evolution process and failure consequences of cyber-physical cascading failures and exploring the internal mechanism of cyber-physical cascading failures have important theoretical and practical significance. Based on the event-driven model,an architecture of power distribution cyber-physical system is proposed to analyze the interaction mechanism between physical and information systems,and a research framework for the evolution mechanism of cyber-physical cascading failures is proposed. Then,the importance of the internal nodes of the information system is studied,the total risk value of the system and the defense resources are comprehensively considered,and the relevant parameters such as the probabilities of the information nodes being successfully attacked are calculated and the correlation matrices are established. Finally,a simulation of the evolution mechanism of cyber-physical cascading failures is carried out on a case,which verifies the rationality of the proposed mechanism and its validity in the deduction of the failure process and the calculation of the consequences.